2017
DOI: 10.1038/nature25157
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of a designed protein assembly encapsulating its own RNA genome

Abstract: The challenges of evolution in a complex biochemical environment—coupling genotype to phenotype and protecting the genetic material—are solved elegantly in biological systems by nucleic acid encapsulation. In the simplest examples, viruses use capsids to surround their genomes. While these naturally occurring systems have been modified to change their tropism1 and to display proteins or peptides2–4, billions of years of evolution have favored efficiency at the expense of modularity, making viral capsids diffic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
237
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 184 publications
(250 citation statements)
references
References 35 publications
(45 reference statements)
3
237
0
Order By: Relevance
“…While previous studies have shown that it is possible to design synthetic protein oligomers either by modifying extant structures [13][14][15][16] or de novo, [8][9][10][11][12] we now show that it may be possible to induce the formation of novel quaternary structures through the simple expedient of supercharging. In so doing, we demonstrate that precise molecular configurations can be obtained by focusing on the driving forces for assembly (charge:charge interactions) rather than the details of the interface.…”
Section: 31mentioning
confidence: 99%
See 4 more Smart Citations
“…While previous studies have shown that it is possible to design synthetic protein oligomers either by modifying extant structures [13][14][15][16] or de novo, [8][9][10][11][12] we now show that it may be possible to induce the formation of novel quaternary structures through the simple expedient of supercharging. In so doing, we demonstrate that precise molecular configurations can be obtained by focusing on the driving forces for assembly (charge:charge interactions) rather than the details of the interface.…”
Section: 31mentioning
confidence: 99%
“…Control SuPrA protomers containing entirely Ceru+32, entirely GFP-17, or an octamer of Ceru+32 juxtaposed with an octamer of GFP-17 were unstable at all NaCl concentrations, consistent with the experimental observations ( Supplementary Fig. 12, 13) Finer-grained structural modeling (i.e., of hydrophobic effects and counterion release) must await specific structural and physical details that should become manifest with further imaging (i.e., cryo-EM) experiments that better determine the precise symmetric arrangement of monomers.While previous studies have shown that it is possible to design synthetic protein oligomers either by modifying extant structures [13][14][15][16] or de novo, [8][9][10][11][12] we now show that it may be possible to induce the formation of novel quaternary structures through the simple expedient of supercharging. In so doing, we demonstrate that precise molecular configurations can be obtained by focusing on the driving forces for assembly (charge:charge interactions) rather than the details of the interface.…”
mentioning
confidence: 99%
See 3 more Smart Citations